Nigella sativa Effects on Neurotransmitter Systems: Potential Treatment for Drug Tolerance and Dependence - Nor Hidayah, Abu Bakar; Abdulsoma, Thoarlim; Muhamad Zaid, Ismail; Nasir, Mohamad (2018)
Drug dependence and tolerance is becoming an enormous health problem worldwide and significantly affect the society. Although currently there are approved drugs used for the treatment of drug dependence and tolerance, these compounds also pose with some notable adverse effects and issues, i.e. drug-dependency and withdrawal problems. Therefore, there are emerging needs for a naturally existing substance such as Nigella Sativa (N. sativa) which can be used as an alternative treatment to treat addiction illness, which may present as natural resources. N. sativa is one of these natural substances that gaind its popularity due to its unique chemical properties. In Islamic literature, N. sativa was mentioned as one of the effective forms of a therapeutic agent and healing medicine. It has promising effects as an anticancer, antioxidant, anti-inflammatory and many other benefits. In addition, several pharmacological research also has been done to investigate the effects of N. sativa bioactive compounds on drug dependence and tolerance. Hence, this review focuses on the effects of N. sativa bioactive compounds on the neurotransmitter systems, and its role in reducing drug dependence and tolerance.